Spatio-temporal characteristics of seismic strain anomalies reveal seismic risk zones along the Longmenshan fault zone and adjacent areas - Luo, Guofu; Xu, Yingcai; Luo, Hengzhi; Ding, Fenghe; Li, Wenjun (Frontiers in Earth Science, 2024)
Identifying and quantifying earthquake precursors, and analyzing their physical mechanisms, continues to be a challenge for earthquake forecasting. In this study, orthogonal functions were developed to effectively identify precursor anomalies, thereby improving the forecasting of strong earthquakes.To study the spatio-temporal contour anomalies in seismic strain fields, we assessed them for seismic activity variables and natural orthogonal function expansion, in six strong earthquakes near the Longmenshan Fault Zone, China, that have occurred since 2008.We observed that, prior to these earthquakes, the temporal factor (the time variation characteristics of the strain field) displayed anomalies with high/low values exceeding the mean square error within a stable context. The anomalies exhibited multi-component characteristics and were primarily concentrated in the first four-strain fields. Short-term and impending-earthquake anomalies were observed in the temporal factor before the 2008 Wenchuan (M8.0) and 2013 Lushan (M7.0) earthquakes, while medium-term and long-term anomalies appeared before the other four strong earthquakes, without notable short-term anomalies. The temporal evolution of strain field contour anomalies, and the strain contours positive and negative intersection, showed that central areas surrounded by multiple strain field contour anomalies were potential locations for strong earthquakes. This suggests a potential approach for earthquake location forecasting. Since 2009, there have been five strong earthquakes, each affected to varying degrees by anomalous strain fields from the 2008 Wenchuan (M8.0) earthquake.The results of this study corroborate the findings of the focal mechanism's node shear stress, indicating significant physical implications of the anomalies and the reliability of these conclusions.